Pengaruh Faktor-faktor Demografi Terhadap Emisi Udara di Indonesia - Zuhri, M. Syaikhuddin (Jurnal Ilmu Ekonomi dan Pembangunan, 2014)
This study aims to determine the influence of demographic factors on air emissions in Indonesia. Demographic factors used in this study were population density, education level, and urbanization rate. Air emissions are measured with carbon dioxide (CO2) emissions as proxies. Theoretically, population density and urbanization levels have a positive effect on air emissions, while technology has a negative effect on air emissions. The analysis technique used is multiple regression using Ordinary Least Square (OLS) method.The results of this study indicate that population density and level of education affect air emissions in accordance with the proposed theory but the level of education does not significantly affect air emissions in Indonesia. Population density, urbanization level, and education level simultaneously affect air emissions in Indonesia. Keywords: air emissions, population density, education, urbanization,JEL Classification: J11, Q53